The Prehistoric Maritime Frontier of Southeast China Indigenous Bai Yue and Their Oceanic Dispersal - Wu, Chunming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book presents multidisciplinary research on the cultural history, ethnic connectivity, and oceanic transportation of the ancient Indigenous Bai Yue ($1!L~!ZM(B) in the prehistoric maritime region of southeast China and southeast Asia. In this maritime Frontier of China, historical documents demonstrate the development of the (3z(Bbarbarian(3y (BBai Yue and Island Yi ($1';y!9,(B) and their cultural interaction with the northern Huaxia ($1'U<!8x(B) in early Chinese civilization within the geopolitical order of the (3z(BCentral State-Four Peripheries Barbarians-Four Seas(3y(B. Archaeological typologies of the prehistoric remains reveal a unique cultural tradition dominantly originating from the local Paleolithic age and continuing to early Neolithization across this border region. Further analysis of material culture from the Neolithic to the Early Iron Age proves the stability and resilience of the indigenous cultures even with the migratory expansion of Huaxia and Han ($1'HW(B) from north to south. Ethnographical investigations of aboriginal heritage highlight their native cultural context, seafaring technology and navigation techniques, and their interaction with Austronesian and other foreign maritime ethnicities. In a word, this manuscript presents a new perspective on the unique cultural landscape of indigenous ethnicities in southeast China with thousands of years$1 (Bstable tradition, a remarkable maritime orientation and overseas cultural hybridization in the coastal region of southeast China. .s
Introduction -- Part I: The Historical Record of the (3z(BBarbarians(3y (BYue and Maritime Yi in the Southeast Frontier of Ancient Chinese Civilization -- Chap.1, (3z(BCentral State- Four Peripheries Barbarians- Four Seas(3y(B: the Spatially Cultural Order of Land-Sea Interaction of Early Chinese Civilization -- Chap.2, Southeastern Peripheries of Huaxia: the Historical Cultural Interaction and Assimilation from (3z(BSouthern Man and Bai Yue(3y (Bto (3z(BIsland Yi and Foreign Maritime Fan(3y (B-- Part II: The Archaeological Exploration on the Prehistoric Cultures in the Maritime Region of Southeast Asia -- Chap.3, The Local Paleolithic Cultural Inheriting of the Maritime Region of Southeast Asia during the Early Neolithization around 10,000 years ago -- Chap.4, The Cultural Influence of Northern Huaxia in the Indigenous System of Geometric Stamped Pattern Pottery Remains of Southeast China During Neolithic, Bronze and Early Iron age -- Part III : The Ethnographical Investigation of the Maritime Cultural Heritages of the Indigenous Yues in Southeast China -- Chap. 5, The Inheritance of Island Yi and the Acculturation of Foreign Maritime Fan: The Cultural History of Maritime Essence of the Han People in South Coast of China -- Chap.6, Ethno-archaeological Analysis on the (3z(BStraw and Bark Weaving(3y (BCulture of Island Yi and Southern Man in Southern China and Southeast Asia -- Chap.7, Searching for the Prehistoric Seafaring Tool between Southeast Coast of China and Pacific Islands -- Chap.8, A Comparative Study of the Astronomical Navigation between Ancient China and Pacific Austronesian -- Part IV: Conclusion -- Chap.9, An Academic Overview on the Research of Cultural Relation of Ancient Indigenous Yue of Southeast Coast of China and Pacific Austronesian.s
Keywords: Underwater archaeology; Prehistoric peoples; Archaeology -- Philosophy; Maritime Archaeology; Prehistoric Archaeology; Archaeology and Race